Early tube leak detection system for steam boiler at KEV power plant - Ismail F.B.; Singh D.; Maisurah N.; Musa A.B.B. (EDP Sciences, 2023)
Backpropagation; Coal; Coal fired boilers; Engineering research; Engines; Fault detection; Fossil fuel power plants; Leak detection; Neural networks; Plant shutdowns; Steam power plants; Artificial neural network models; Coal-fired power plant; Feed-forward back propagation networks; Hidden layers; Neural network (nn); Training algorithms; Training function; Working properties; Boilers